2019
DOI: 10.1021/acsapm.9b00967
|View full text |Cite
|
Sign up to set email alerts
|

Improved Fluorescence and Brightness of Near-Infrared and Shortwave Infrared Emitting Polymer Dots for Bioimaging Applications

Abstract: Development of near-infrared (NIR) and shortwave infrared (SWIR) emitting fluorophores is central to the fluorescence-based bioimaging. While conjugated polymer nanoparticles (polymer dots) are one of the promising fluorophores for this application, obtaining polymer dots that show bright fluorescence, especially in the SWIR wavelength region, has been challenging. Here, we report generalized approach to obtain bright polymer dots through a systematic characterization of photophysical properties of NIR and SWI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 68 publications
0
44
0
Order By: Relevance
“…1,2 Conjugated polymer nanoparticles have shown great potential as contrast agents in fluorescence and photoacoustic imaging. [3][4][5][6] Compared to small molecular contrast agents nanoparticles are advantageous in their high fluorescence and photostability. [7][8][9] In addition to their outstanding optical properties, nanoparticles of conjugated polymers can be used for passive targeting, where they make use of the enhanced permeation and retention (EPR) effect.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Conjugated polymer nanoparticles have shown great potential as contrast agents in fluorescence and photoacoustic imaging. [3][4][5][6] Compared to small molecular contrast agents nanoparticles are advantageous in their high fluorescence and photostability. [7][8][9] In addition to their outstanding optical properties, nanoparticles of conjugated polymers can be used for passive targeting, where they make use of the enhanced permeation and retention (EPR) effect.…”
Section: Introductionmentioning
confidence: 99%
“…30 We recently reported a new generalized strategy for obtaining Pdots that exhibit bright SWIR fluorescence by integrating the rational design and synthesis of CPs; we also optimized the fabrication protocol for Pdots. 34 Here, we report single-particle fluorescence imaging of SWIR-emitting Pdots. We show that ultrasmall (as small as 3.5 nm) SWIR-emitting Pdots exhibit much brighter (5× brighter) fluorescence compared with frequently used semiconductor quantum dots (e.g., PbS QDs) under typical experimental conditions for single-molecule imaging.…”
mentioning
confidence: 96%
“…[27][28][29][30][31] In addition to their high biocompatibility, 32 Pdots can be reliably prepared as ultrasmall (<5 nm) NPs using proper protocols. 33,34 Thus, Pdots are promising fluorescent NPs for single-particle SWIR imaging. Researchers have developed small-bandgap CPs with a large extinction coefficient by designing DAD-type CPs that exhibit strong intramolecular charge transfer absorption and fluorescence.…”
mentioning
confidence: 99%
“…Even though it is challenging to shift conjugated polymers to the NIR region, recent studies using conjugated donor–acceptor fluorophore systems showed remarkable examples exhibiting high brightness and good in vivo imaging contrast. 18,19 However, these systems owing to their structures remain essentially non-biodegradable NPs. Another approach is to use biodegradable polymeric NPs 2,20 as a nanocarrier of dyes.…”
Section: Introductionmentioning
confidence: 99%